The importance of the rate of pure "attended deaths at home" for objective outcome indicator for assessing the prevalence of home care in Japan - Yasuhiro Kakiuchi; Ryoko Nagao; Eriko Ochiai; Yu Kakimoto; Motoki Osawa (Komiyama Printing Co. Ltd, 2019)
Abstract Background No study has yet been performed on the importance of the rate of pure "attended deaths at home," excluding examined deaths subjected to a postmortem examination. Therefore, in the present study, we investigated actual state of pure "attended deaths at home," in order to provide reference data for the future development of end-of-life care at home. Methods We performed a detailed survey in Yokohama City according to the type of death, age, and underlying cause of death in cases of home deaths, based on the detailed version of the Vital Statistics Survey Death Forms. Then, we divided deaths occurring in each municipality in Kanagawa Prefecture into two categories: "examined deaths" or "attended deaths," which were also stratified by the place of death, based on the Vital Statistics, and data on number of death cases subjected to postmortem examination from the Kanagawa Prefectural Police Headquarters. Results In 2013, the survey in Yokohama City showed large differences in age distribution and cause of death between examined and attended deaths. In 2014, home deaths accounted for 15.7% of all deaths in the prefecture, whereas the overall proportion of attended deaths at home was 6.9%. Conclusions We should utilize the rate of pure "attended deaths at home" for objective outcome indicator.